2017
DOI: 10.3389/fnbeh.2017.00122
|View full text |Cite
|
Sign up to set email alerts
|

Using Virtual Reality to Assess Ethical Decisions in Road Traffic Scenarios: Applicability of Value-of-Life-Based Models and Influences of Time Pressure

Abstract: Self-driving cars are posing a new challenge to our ethics. By using algorithms to make decisions in situations where harming humans is possible, probable, or even unavoidable, a self-driving car's ethical behavior comes pre-defined. Ad hoc decisions are made in milliseconds, but can be based on extensive research and debates. The same algorithms are also likely to be used in millions of cars at a time, increasing the impact of any inherent biases, and increasing the importance of getting it right. Previous re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
49
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 30 publications
13
49
0
Order By: Relevance
“…Results from our studies on moral judgement generally align with those from previous studies of moral action, in which participants were in the roles of drivers in similar dilemma scenarios (Sütfeld et al, 2017;Faulhaber et al, 2018). This indicates that the discrepancy between moral action and moral judgement (shown by e.g., Francis et al, 2016) may not be extremely pronounced in driving-related dilemmas presented in virtual environments.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Results from our studies on moral judgement generally align with those from previous studies of moral action, in which participants were in the roles of drivers in similar dilemma scenarios (Sütfeld et al, 2017;Faulhaber et al, 2018). This indicates that the discrepancy between moral action and moral judgement (shown by e.g., Francis et al, 2016) may not be extremely pronounced in driving-related dilemmas presented in virtual environments.…”
Section: Discussionsupporting
confidence: 87%
“…For the three scenarios, patterns of judgements aligned with actions taken in similar dilemma studies reported by Faulhaber et al (2018) (further elaborated by Bergmann et al, 2018) and Sütfeld et al (2017): participants generally preferred motorists to risk the lives of adult pedestrians rather than child pedestrians, despite endangering more lives by doing so; it was highly acceptable for a motorist to swerve onto a sidewalk in order to endanger fewer pedestrians; and there was a tendency to protect pedestrians over car occupants. However, it seems that the perceived danger to the car occupants plays a role; participants were less likely to accept a car veering toward a cliff edge, than a car veering toward a parked van.…”
Section: Study 1 Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Due to the emergence of autonomous vehicles, this kind of situations is more and more studied in order to investigate which behaviours are admissible in this case. Sütfeld et al (2017), for example, conducted a study in which they exposed the drivers to various virtual situations of inevitable collisions. Dilemmas are also used in training simulations.…”
Section: Related Workmentioning
confidence: 99%